Exploring culture theory global leadership and organizational behaviour effectiveness in cross-cultural communication in Asian business negotiations - Pin, Lick Soo Hoo (2016)
While certain in international business negotiations, having the knowledge of cross-cultural communication is essential especially in global business environments and thus, many researchers have spent numerous years to investigate how culture influences Asian business negotiation which has contributed to negotiation outcome.This article provides critical insight into the theoretical link of cultural dimensions of culture for international business negotiations.The proposed model suggested in this study helps to identify effective communicative behaviours in business negotiations which are useful insights for international business practitioners.